Biomechanics of the Cornea Assessed by the CorVis ST ® Device: a Numerical Approach - Ariza, Miguel Ángel; Rodríguez, José F.; Calvo, Begoña (Jornada de Jóvenes Investigadores del I3A, 2017)
To evaluate by means of finite element modeling the influence of tissue properties of the cornea on its deformation response when an air jet is applied onto its surface and, according to this, to discuss the clinical interpretation of these measurements in terms of corneal biomechanical behaviour.